Pengaruh Customer Experience Terhadap Repurchase Intention Pada PT. Traveloka Indonesia - Aulia Cahyani; I Made Adhi Gunadi; Yustisia Pasfatima Mbulu (Politeknik Sahid, 2019)
Online Travel Agent is an online based travel agent that provides tourism products and services, such as hotel review, prices, features, and reservation. At present day, online Travel Agent is growing rapidly with many playesr and various types in Indonesia. PT. Traveloka Indonesia is one of the key player in the business. This study aims to identify customer experience at PT. Traveloka Indonesia and analyze the effect of customer experience on repurchase intention at PT. Traveloka Indonesia. The research design used is quantitative with multiple linear regression data analysis techniques. The results show that all customer experience variables which derived from Nilsson and Wall (2017) have a significant effect simultaneously on the repurchase intention variable. While partially, five customer experience variables namely ease of use, customer review, security, customer service, and store offerings significantly influence the repurchase intention at PT. Traveloka Indonesia. Whereas the other two, namely customization and reliability fulfillment, have no significant effect on repurchase intention at PT. Traveloka Indonesia.